THE IMPACT OF COMPANY LIFECYCLE ON ACCOUNTING EARNINGS MANAGEMENT: AN APPLIED STUDY ON A SAMPLE OF IRAQI BANKS (World Economics and Finance Bulletin, 2024)
The current study aimed to determine the impact of a company's lifecycle and the phases it goes through on the management of accounting profits in the Iraqi environment. This research relied on cash flows to measure the company's lifecycle using age-based indicators, defined as follows: a company is in the introduction phase if it is less than 10 years old; if sales growth exceeds 15%, the company is in the growth phase; and if growth is negative, the company is in the decline phase. To measure the management of accounting profits, the study used a non-discretionary accruals model, specifically the modified Jones model. Additionally, content analysis was adopted to gather data from a sample of 10 banks listed on the Iraq Stock Exchange over 10 years, from 2013 to 2022, resulting in 100 observations (bank/year). Moreover, the research adopted a descriptive-analytical approach to prepare and test its hypothesis. The research concluded that there is a significant positive impact of the company's lifecycle on the management of accounting profits among the banks in the sample. This implies that as banks progress through their lifecycle phases from introduction to growth, then maturity, and finally decline, they tend to increasingly adopt accounting profit management practices
Keywords: Company Lifecycle; Accounting Profit Management; Banking Sector